Exploring the Usage of Conjunctions in Barack Obama’s Inaugural Victory Speech Delivered at Grant Park, Chicago - Aji, Muhammad Najib Kurnia (English Language and Literature in Education Journal, 2024)
This descriptive qualitative study aimed to analyze the types and functions of coordinate conjunctions in Barack Obama’s first victory speech delivered at Grant Park, Chicago. Utilizing a scripted transcript of the speech as the primary data source, the research meticulously identified instances where coordinate conjunctions appeared in words, phrases, or sentences. The study revealed that the most frequently used type of coordinate conjunction was ‘and’, which accounted for 113 instances (83.09%) of all occurrences. These conjunctions predominantly served to join individual words, link groups of words, and connect parts within compound sentences. The implications of the findings are twofold: first, English educators are encouraged to prioritize providing clear explanations of conjunctions to enhance students’ grammatical proficiency. Understanding how conjunctions function in speech can significantly improve students’ ability to construct coherent sentences and express ideas effectively. Second, students are urged to actively apply their knowledge of conjunctions during their learning processes to reinforce their language skills. By practicing the identification and usage of conjunctions in both spoken and written contexts, students can develop greater fluency and accuracy in their communication. Furthermore, the study suggests avenues for future research to explore the application and functions of different types of conjunctions across various discourse contexts. This exploration could deepen our understanding of how conjunctions contribute to the structure and coherence of language, thereby enriching language education practices and advancing linguistic research. Overall, this research contributes to both theoretical insights into speech analysis and practical implications for language teaching and learning.